FATWA MAJELIS ULAMA INDONESIA DAN TANTANGAN OTORITAS KEAGAMAAN BARU DI ERA DIGITAL - Achmad Muhibin Zuhri (Universitas Kiai Abdullah Faqih Gresik, 2022)
The Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) is a clerical institution tasked with issuing fatwas. On the one hand, these fatwa products can occasionally help Muslims with their internal issues, but on the other, MUI fatwa products serve as a vehicle for some groups to justify intolerable behavior. This article is included in the study of Islamic thought using a digital sociology perspective. Research information was found by looking up MUI fatwas in a number of incidents that had an effect on society in Internet news publications. According to this study, the virtual community (netizens) prefer Ustaz who is popular on social media over Ustaz from a variety of established religious organizations. The results of this study show that the MUI authority must prioritize setting and social impact when packaging fatwas. MUI fatwa products should be disseminated through social media platforms (Youtube, Facebook, Instagram, and Twitter). Its function is to target a wider congregation so that their understanding of Islam is in accordance with the objectives of the Shari‘a (maqasid al-shari‘ah). In addition, the packaging of fatwas is needed so that religious texts are understood more easily but do not eliminate the legal substance and socio-cultural considerations in a heterogeneous society.